OPINI AUDIT GOING CONCERN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - I Ketut Sunarwijaya; I Putu Edy Arizona (Jurnal Widya Akuntansi dan Keuangan, 2019)
Going concern audit opinion is an opinion issued by the auditor because there are several factors in maintaining going concern of the company. Opinion audit going concern be one example for users of financial statements to be used in decision making. This study aims to determine the effect of cash, liquidity, leverage, audit lag, auditor switching, company growth, and company size on audit audits. This research was conducted on companies that produce on the Indonesia Stock Exchange in 2014-2017. The sampling technique used was purposive sampling technique with the number of research samples as much as 117. The data analysis techniques were logistic regression techniques. The results showed that the variables of cash, liquidity, leverage, audit leg, switching auditors, company growth, and size did not affect the audit.